FREQUENT LANGUAGE LEARNING STRATEGIES USED BY SUCCESSFUL LEARNERS - Ima Isnaini Taufiqur Rohmah (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2017)
The main factors that help determining students learn a foreign language is their strategies used in learning. This article aims to describe the most frequent learning strategies applied by students categorized as good learners that help them learn English effectively. This research is under qualitative case study which is conducted on three students from the first grade of Economic Education Study Program of IKIP PGRI Bojonegoro categorized as good learners of English. To get the detail of data in depth interviews, observation, questionnaires, and document analysis were used. The result of this study reveals that cognitive strategies and memory strategies were the strategies that often used by the student in learning English. These learning strategies employed the student gained best mark in each English test and could improve speaking skill. By applying those learning strategies, they always got good score in English lesson. Thus, in learning English as a foreign language, good language learning strategies are required. Key words: case study, learning strategies, successful learner